THE FUTSAL PHENOMENON IN SCHOOL: ANALYSIS OF CULTURAL EXPRESSIONS IN THIS CLASSROOM PHYSICAL EDUCATION (Fiep Bulletin - online, 2015)
This text refers to the futsal phenomenon found in Physical Education. Based on the literature review, we sought to understand through the historical and cultural recovery mode on the facts that led to the dominance of this sport in schools and beyond. Starting addition, teachers end up suffering aversion on the part of the students by providing different activities and thus become hostages often this practice. Inhibiting the ability of the child to experience other manipulative movements that involve the ball, thus helping more and more to that futsal is seens as the only content of Physical Educations classes.
Keywords: Body Culture; Physical Education; Futsal